Structural and electrochemical properties of lini0.4Co 0.4-Xal0.2+Xo2 cathode materials for lithium-ion batteries - Basirun, Wan Jefrey; Arof, Abdul Kariem; Sethuprakhash, V. (Springer Verlag (Germany), 2005)
Three Al doped lithium nickel cobalt oxide (LiNi0.4Co 0.4-xAl0.2+xO2) cathode materials for lithium ion batteries were synthesized by solid state reaction method at a temperature of 800 °C for 18 hours. The samples were crystalline as revealed by powder X-Ray diffraction (XRD). The ratios of the elements were determined by Energy Dispersive Analysis of X-rays (EDAX). The electrochemical properties obtained by charge/discharge cycling showed that the average discharge capacity for LiNi0.4Co0.4Al0.2O2 was 117 mAh/g. A good capacity retention was also shown by the material upon cycling.